Cutaneous presentation preceding acute monocytic leukemia: A CARE-compliant article. Issue 10 (March 2017) - Jin, Xianhua; Li, Fuqiu; Li, Xue; Zhu, Wenjing; Mou, Yan; Huang, Yang; Zhao, Huanyu; Gao, Wei; Xia, Jianxin
Abstract: Rationale: Cutaneous presentation preceding acute myeloid leukemia (AML) is rare, and the prognosis is poor. Patient concerns: We report 4 cases of AML cutis, where skin infiltration precedes any blood or bone marrow evidence of leukemia. We also reviewed 13 cases reported in English and Chinese literature. The 4 cases all presented typical cutaneous lesions without any systemic evidence of leukemia. Histopathological examination found that dense monomorphous cell infiltration involved the dermis. Some cells surrounded blood vessels and skin appendages in a concentric manner or showed single-row arrangement in the collagen fiber bundles. Uninvolved papillary dermis was found to separate normal epidermis from dermal infiltration. Minor cells had a large kidney-shaped or oval nucleus with nucleoli and slightly eosinophilic cytoplasm. Immunohistochemical analysis was positive for CD4, CD56, while CD123 was negative in all cases. Diagnoses: AML-M5. Interventions: 2 patients received chemotherapy, but others rejected treatment. Outcomes: Most patients died within 1 year after the onset of skin lesions. Lessons: These findings suggest that skin infiltration of AML may precede any systemic evidence, and typical cutaneous lesions in elderly individuals may be indicative for AML.